Ketersediaan Biomassa Pada Berbagai Jenis Klon Karet (Hevea brasiliensis) di Lahan Kering - Achnopha, Yudhi; Safitri, Lilian (Jurnal Pertanian Terpadu, 2023)
Biomass is the total weight or volume of organisms in a certain area or volume that live above the surface of a tree. Biomass is used as a way of determining climate mitigation projects as well as other improvements such as deforestation and other agroforestry activities. This research was carried out in January 2023 in rubber farmers' fields where there were various types of clones that could be observed for the amount of biomass produced. This study used a randomized block design with 10 treatments (in the form of clones) and 3 groups. The types of clones are (1) RRIC 100 clone; (2) PR 255 clone; (3) Clone BPM 109; (4) Clone PB 217; (5) Clone BPM 1; (6) Clone PR 261; (7) Origin of seeds; (8) Clone BPM 107; (9) Clone PB 260; and (10) Clone GT 1. By using the equation Y = -3.84 + (0.528 x BA) + (0.001 x BA2) the highest amount of biomass was obtained in clone PB 217 as much as 25.23 kg/tree, clones from seeds as many as 24.08 kg/tree and clone type GT 1 as much as 24.07 kg/tree. The measured biomass content is part of the activities of plant organisms that decompose evenly throughout the plant.